2012
DOI: 10.3390/en5104233
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Thiophenic Compounds from Model Diesel Fuel Using Copper and Nickel Impregnated Activated Carbons

Abstract: Adsorption of sulfur compoundsby porous materials is an effective way to produce cleaner diesel fuel.In this study, adsorption of refractory thiophenic sulfur compounds, i.e., benzothiophene (BT), dibenzothiophene (DBT), and 4,6-dimethyldibenzothiophene (4,6-DMDBT) in single-solute systems from n-hexane solutions onto metal-impregnated activated carbons was investigated. A hydrogen-treated activated carbon fiber was selectively loaded with Ni, NiO, Cu, Cu 2 O, and CuO species to systematically assess the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 51 publications
(110 reference statements)
1
21
0
Order By: Relevance
“…Typically, AC is mostly microporous in nature and there are efforts to create mesoporosity in it for extended applications [31]. The obtained commercial AC contained both mesopores and micropores, with high surface area greater than 1000 m 2 /g, wherein external surface area accounted for more than 60%.…”
Section: Textural Properties Of Adsorbentsmentioning
confidence: 99%
“…Typically, AC is mostly microporous in nature and there are efforts to create mesoporosity in it for extended applications [31]. The obtained commercial AC contained both mesopores and micropores, with high surface area greater than 1000 m 2 /g, wherein external surface area accounted for more than 60%.…”
Section: Textural Properties Of Adsorbentsmentioning
confidence: 99%
“…This is mainly because of the low sulfur uptake ability of the adsorbent material when the percentage of sulfur content in the oil fractions of interest is put into consideration. Another major setback of this adsorption method is the presence of competitive adsorption of aromatics and olefins, which results in a decrease in the sulfur uptake by the adsorbent [104][105][106]. Therefore, studies have suggested the use of pre-adsorbent for removing larger organo-sulfur molecules.…”
Section: Physical Adsorptionmentioning
confidence: 99%
“…Among them, Mn-and Ce-based catalysts have drawn particular attention due to their abundant oxygen vacancies, which promote the redox cycle during SCR reactions [11][12][13][14]. In addition, activated carbon (AC) has been used as catalyst support for SCR, since it has high surface for metal loading and the presence of functional groups on the surface of activated carbon can also promote NO x conversion [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%